2016
DOI: 10.1007/s13197-016-2184-1
|View full text |Cite
|
Sign up to set email alerts
|

Argentinian pistachio oil and flour: a potential novel approach of pistachio nut utilization

Abstract: In order to searching a potential novel approach to pistachio utilization, the chemical and nutritional quality of oil and flour from natural, roasted, and salted roasted pistachios from Argentinian cultivars were evaluated. The pistachio oil has high contents of oleic and linoleic acid (53.5 - 55.3, 29 - 31.4 relative abundance, respectively), tocopherols (896 - 916 μg/g oil), carotenoids (48 - 56 μg/g oil) and chlorophylls (41 - 70 μg/g oil), being a good source for commercial edible oil production. The proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 31 publications
5
22
2
Order By: Relevance
“…They are apolar compounds easily soluble in the fat fraction, and therefore, the increase in temperature during the extraction process does not significantly favor their solubility. This is in agreement with results from Martínez et al that did not find significant differences in tocopherol content among raw and roasted pistachios. Indeed, tocopherols have been reported to be resistant to thermal degradation, and moreover, a better extractability of these compounds due to the heating treatment has also been described …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are apolar compounds easily soluble in the fat fraction, and therefore, the increase in temperature during the extraction process does not significantly favor their solubility. This is in agreement with results from Martínez et al that did not find significant differences in tocopherol content among raw and roasted pistachios. Indeed, tocopherols have been reported to be resistant to thermal degradation, and moreover, a better extractability of these compounds due to the heating treatment has also been described …”
Section: Resultsmentioning
confidence: 99%
“…Due to the observed behavior, pigments could be considered as an index of the extraction of minor compounds, since their concentrations in the oil increase with a trend reasonable similar to bioactive compounds (like TPP in Figure ). This behavior was also observed by Martínez et al who reported a higher pigment concentration in oils obtained from roasted pistachios compared to fresh ones and found an increase in chlorophylls over carotenoids. However, Pumilia et al and Aparicio‐Ruiz et al demonstrated that the thermal process induces degradation of chlorophylls into derivative compounds such as pheophytins.…”
Section: Resultsmentioning
confidence: 99%
“…Pistachio kernels from commercial cultivars yield 50–60% oil. [ 96–98 ] Significant genotypic variations in oil contents are found from genetic resources worldwide. Various pistachio genotypes cultivated in Spain show oil yields ranging from 40.7 to 54.7 g per 100 g kernel.…”
Section: Chemistry and Quality Of Nut Oilsmentioning
confidence: 99%
“…[ 100,101 ] Contrarily, the oil content from kernels of the cv. Kerman—which is one of the most widespread pistachio cultivar worldwide—appears to be relatively stable across environments; oil yields ranging from 48.1% to 50.1% have been obtained from orchards located in Spain, [ 99 ] Argentina, [ 98 ] and the USA. [ 102 ]…”
Section: Chemistry and Quality Of Nut Oilsmentioning
confidence: 99%
“…Other sources are fruits, such as grapes and blackberries, apples, or nuts like beans, almond, pistachos, and red wine (Bhagwat, Haytowitz, & Holden, 2014;Cassino, Tsolakis, Bonello, Gianotti, & Osella, 2019;Gadkari & Balaraman, 2015;Harnly et al, 2006;Martinez et al, 2016).…”
Section: Flavanolsmentioning
confidence: 99%